Legal Remedies in Civil Law for Document Forgery: a Case Study in Indonesia and Comparative Analysis with ASEAN Countries - Maharani Millenia Hussy (PT Publikasiku Academic Solution, 2024)
The prevalence of deed forgery practices to benefit one party at the expense of another has been observed frequently. Consequently, the aggrieved party needs to pursue civil legal remedies to seek compensation. Indonesia adheres to the theory that legal remedies come in two forms: preventive legal measures and repressive legal measures. Legal provisions concerning deed forgery fall under preventive legal measures while filing a civil lawsuit with the Kepanjen District Court is considered a repressive legal measure. The objective of this research is to discuss civil legal remedies for deed forgery based on the verdict in Case Number 55/Pdt.G/2021/Pn.Kpn from the Kepanjen District Court, East Java, Indonesia, and compare them with other relevant laws from other ASEAN countries (i.e., Malaysia, Philippines, Brunei Darussalam, Singapore, Thailand, Vietnam, and Myanmar). This study is conducted as there is limited discussion on deed forgery from the perspective of civil law. The research method employed is the normative legal research method, involving an examination of the Civil Code and a case study of the mentioned verdicts. The research findings indicate that the legal remedies in these verdicts fulfill the elements of legal protection theory